Tensions between China, North Korea and the United States at the beginning of the Trump administration - Eduardo Tzili Apango (Estudios de Asia y África, 2018)
The Trump administration has been characterized by its aggressive rhetoric against North Korea. The escalation in the tone of the discourse reached a critical point with Trump’s “Fire and fury” declaration, to which Kim Jong-un answered by characterizing Trump as a “dotard”, and then testing a hydrogen bomb. The rise of tensions in the Korean peninsula is due to divergent formation of identities and perceptions among the actors involved. The main hypothesis of this article is that, because of the lack of progress in de- nuclearizing the Korean Peninsula, the Trump’s government has employed bold and aggressive rhetoric that it hopes will affect the unstable status quo in the region and lead to it meeting its goal of economic benefits from Beijing and the benefits of an improved security relation with Pyongyang.